Location via proxy:   [ UP ]  
[Report a bug]   [Manage cookies]                
SlideShare a Scribd company logo
2.7 Combining Functions


John 16:33 I have said these things to you, that in me you
may have peace. In the world you will have tribulation. But
take heart; I have overcome the world.”
We can add, subtract, multiply, divide functions
We can add, subtract, multiply, divide functions

       f (x) + g(x) = ( f + g)(x)   D : D f I Dg
We can add, subtract, multiply, divide functions

       f (x) + g(x) = ( f + g)(x)   D : D f I Dg

       f (x) − g(x) = ( f − g)(x)   D : D f I Dg
We can add, subtract, multiply, divide functions

       f (x) + g(x) = ( f + g)(x)   D : D f I Dg

       f (x) − g(x) = ( f − g)(x)   D : D f I Dg

       f (x)⋅ g(x) = ( f ⋅ g)(x)    D : D f I Dg
We can add, subtract, multiply, divide functions

       f (x) + g(x) = ( f + g)(x)   D : D f I Dg

       f (x) − g(x) = ( f − g)(x)   D : D f I Dg

       f (x)⋅ g(x) = ( f ⋅ g)(x)    D : D f I Dg

      f (x) ⎛ f ⎞                 D : D f I Dg
           = ⎜ ⎟ ( x )
      g(x) ⎝ g ⎠                        and
                                        g(x) ≠ 0
x−4           x−3
Example:   f (x) =        g(x) =
                   x −1          x−2
x−4            x−3
Example:     f (x) =         g(x) =
                     x −1           x−2
                x−4 x−3
  ( f + g)(x) =     +            D:   {x : x ≠ 1,2}
                x −1 x − 2
x−4            x−3
Example:     f (x) =         g(x) =
                     x −1           x−2
                x−4 x−3
  ( f + g)(x) =     +            D:   {x : x ≠ 1,2}
                x −1 x − 2
                x−4 x−3
  ( f − g)(x) =     −            D:   {x : x ≠ 1,2}
                x −1 x − 2
x−4                x−3
Example:          f (x) =             g(x) =
                          x −1               x−2
                x−4 x−3
  ( f + g)(x) =     +                     D:   {x : x ≠ 1,2}
                x −1 x − 2
                x−4 x−3
  ( f − g)(x) =     −                     D:   {x : x ≠ 1,2}
                x −1 x − 2

                ⎛ x − 4 ⎞ ⎛ x − 3 ⎞
  ( f ⋅ g)(x) = ⎜
                ⎝ x − 1 ⎟ ⎜ x − 2 ⎟
                         ⎠ ⎝       ⎠
                                          D:   {x : x ≠ 1,2}
x−4                   x−3
Example:           f (x) =                g(x) =
                           x −1                  x−2
                x−4 x−3
  ( f + g)(x) =     +                         D:   {x : x ≠ 1,2}
                x −1 x − 2
                x−4 x−3
  ( f − g)(x) =     −                         D:   {x : x ≠ 1,2}
                x −1 x − 2

                ⎛ x − 4 ⎞ ⎛ x − 3 ⎞
  ( f ⋅ g)(x) = ⎜
                ⎝ x − 1 ⎟ ⎜ x − 2 ⎟
                         ⎠ ⎝       ⎠
                                              D:   {x : x ≠ 1,2}

  ⎛ f ⎞       ⎛ x − 4 ⎞ ⎛ x − 2 ⎞
  ⎜ g ⎟ (x) = ⎜ x − 1 ⎟ ⎜ x − 3 ⎟
                ⎝       ⎠ ⎝       ⎠
                                              D:   {x : x ≠ 1,2, 3}
  ⎝ ⎠
x−4                   x−3
Example:           f (x) =                g(x) =
                           x −1                  x−2
                x−4 x−3
  ( f + g)(x) =     +                         D:   {x : x ≠ 1,2}
                x −1 x − 2
                x−4 x−3
  ( f − g)(x) =     −                         D:   {x : x ≠ 1,2}
                x −1 x − 2

                ⎛ x − 4 ⎞ ⎛ x − 3 ⎞
  ( f ⋅ g)(x) = ⎜
                ⎝ x − 1 ⎟ ⎜ x − 2 ⎟
                         ⎠ ⎝       ⎠
                                              D:   {x : x ≠ 1,2}

  ⎛ f ⎞       ⎛ x − 4 ⎞ ⎛ x − 2 ⎞
  ⎜ g ⎟ (x) = ⎜ x − 1 ⎟ ⎜ x − 3 ⎟
                ⎝       ⎠ ⎝       ⎠
                                              D:   {x : x ≠ 1,2, 3}
  ⎝ ⎠

  Be sure to read Example 2 in your textbook
Composite Functions
Composite Functions
The output of one function (the inner function)
is used as input for another function (the
outer function)    notation : f ( g ( x ))
Composite Functions
 The output of one function (the inner function)
 is used as input for another function (the
 outer function)    notation : f ( g ( x ))
Example 1:    y = x +1
Composite Functions
 The output of one function (the inner function)
 is used as input for another function (the
 outer function)    notation : f ( g ( x ))
Example 1:    y = x +1
 Inner function is done first        x +1

 Outer function is done second        x
Composite Functions
 The output of one function (the inner function)
 is used as input for another function (the
 outer function)    notation : f ( g ( x ))
Example 1:    y = x +1
 Inner function is done first        x +1

 Outer function is done second        x
             g(x) = x + 1
             f (x) = x
             f (g(x)) = x + 1
Composite Functions

Example 2:    y = sin ( 3θ )
Composite Functions

Example 2:        y = sin ( 3θ )

  Inner      3θ                    g(θ ) = 3θ
Composite Functions

Example 2:        y = sin ( 3θ )

  Inner      3θ                    g(θ ) = 3θ

  Outer      sin ( x )             f (x) = sin ( x )
Composite Functions

Example 2:        y = sin ( 3θ )

  Inner      3θ                    g(θ ) = 3θ

  Outer      sin ( x )             f (x) = sin ( x )

                  f (g(θ )) = sin ( 3θ )
Composite Functions

Example 3:    y = sin 2 (θ )
Composite Functions

Example 3:       y = sin 2 (θ )

  Inner      sin (θ )             g(θ ) = sin (θ )
Composite Functions

Example 3:           y = sin 2 (θ )

  Inner      sin (θ )                 g(θ ) = sin (θ )

  Outer      x   2
                                      f (x) = x   2
Composite Functions

Example 3:           y = sin 2 (θ )

  Inner      sin (θ )                 g(θ ) = sin (θ )

  Outer      x   2
                                      f (x) = x   2




                     f (g(θ )) = sin 2 (θ )
Composite Functions

Example 4:    y = sin 2 ( 3θ )
Composite Functions

Example 4:     y = sin 2 ( 3θ )

  Innermost         3θ            h(θ ) = 3θ
Composite Functions

Example 4:     y = sin 2 ( 3θ )

  Innermost         3θ            h(θ ) = 3θ

  Next Inner       sin (θ )       g(θ ) = sin (θ )
Composite Functions

Example 4:     y = sin 2 ( 3θ )

  Innermost         3θ            h(θ ) = 3θ

  Next Inner       sin (θ )       g(θ ) = sin (θ )

  Outer             x   2
                                  f (x) = x 2
Composite Functions

Example 4:     y = sin 2 ( 3θ )

  Innermost         3θ               h(θ ) = 3θ

  Next Inner       sin (θ )          g(θ ) = sin (θ )

  Outer             x   2
                                     f (x) = x 2

                    f (g(h(θ ))) = sin 2 ( 3θ )
Composite Functions

Example 4:     y = sin 2 ( 3θ )

  Innermost         3θ               h(θ ) = 3θ

  Next Inner       sin (θ )          g(θ ) = sin (θ )

  Outer             x   2
                                     f (x) = x 2

                    f (g(h(θ ))) = sin 2 ( 3θ )


 Be sure to read Example 7 in your textbook
Is f (g(x)) = g( f (x)) ?
Is f (g(x)) = g( f (x)) ?   Let f(x) = 2x+1
                                g(x) = x-3
Is f (g(x)) = g( f (x)) ?     Let f(x) = 2x+1
                                  g(x) = x-3

    f (g(x)) = 2(x − 3) + 1
            = 2x − 6 + 1
            = 2x − 5
Is f (g(x)) = g( f (x)) ?     Let f(x) = 2x+1
                                    g(x) = x-3

    f (g(x)) = 2(x − 3) + 1   g( f (x)) = (2x + 1) − 3
            = 2x − 6 + 1               = 2x − 2
            = 2x − 5
Is f (g(x)) = g( f (x)) ?      Let f(x) = 2x+1
                                     g(x) = x-3

    f (g(x)) = 2(x − 3) + 1    g( f (x)) = (2x + 1) − 3
            = 2x − 6 + 1                = 2x − 2
            = 2x − 5

                        Not the same
Is f (g(x)) = g( f (x)) ?      Let f(x) = 2x+1
                                     g(x) = x-3

    f (g(x)) = 2(x − 3) + 1    g( f (x)) = (2x + 1) − 3
            = 2x − 6 + 1                = 2x − 2
            = 2x − 5

                        Not the same
                Could they be the same?
Could f (g(x)) = g( f (x)) ?
Could f (g(x)) = g( f (x)) ?
                                           x −1
             Let f (x) = 2x + 1 and g(x) =
                                             2
Could f (g(x)) = g( f (x)) ?
                                              x −1
                Let f (x) = 2x + 1 and g(x) =
                                                2

                 ⎛ x − 1 ⎞
    f (g(x)) = 2 ⎜       ⎟ + 1
                 ⎝ 2 ⎠

             = x − 1+ 1

             =x
Could f (g(x)) = g( f (x)) ?
                                              x −1
                Let f (x) = 2x + 1 and g(x) =
                                                2

                 ⎛ x − 1 ⎞                   (2x + 1) − 1
    f (g(x)) = 2 ⎜       ⎟ + 1   g( f (x)) =
                 ⎝ 2 ⎠                            2
                                               2x
             = x − 1+ 1                      =
                                                2
             =x                             =x
Could f (g(x)) = g( f (x)) ?
                                              x −1
                Let f (x) = 2x + 1 and g(x) =
                                                2

                 ⎛ x − 1 ⎞                   (2x + 1) − 1
    f (g(x)) = 2 ⎜       ⎟ + 1   g( f (x)) =
                 ⎝ 2 ⎠                            2
                                               2x
             = x − 1+ 1                      =
                                                2
             =x                             =x

    These are the same. It happens when f(x)
       and g(x) are inverses of each other.
HW #9

“There are precious few Einsteins among us.
Most brilliance arises from ordinary people
working together in extraordinary ways.”
                              Roger Von Oech

More Related Content

0210 ch 2 day 10

  • 1. 2.7 Combining Functions John 16:33 I have said these things to you, that in me you may have peace. In the world you will have tribulation. But take heart; I have overcome the world.”
  • 2. We can add, subtract, multiply, divide functions
  • 3. We can add, subtract, multiply, divide functions f (x) + g(x) = ( f + g)(x) D : D f I Dg
  • 4. We can add, subtract, multiply, divide functions f (x) + g(x) = ( f + g)(x) D : D f I Dg f (x) − g(x) = ( f − g)(x) D : D f I Dg
  • 5. We can add, subtract, multiply, divide functions f (x) + g(x) = ( f + g)(x) D : D f I Dg f (x) − g(x) = ( f − g)(x) D : D f I Dg f (x)⋅ g(x) = ( f ⋅ g)(x) D : D f I Dg
  • 6. We can add, subtract, multiply, divide functions f (x) + g(x) = ( f + g)(x) D : D f I Dg f (x) − g(x) = ( f − g)(x) D : D f I Dg f (x)⋅ g(x) = ( f ⋅ g)(x) D : D f I Dg f (x) ⎛ f ⎞ D : D f I Dg = ⎜ ⎟ ( x ) g(x) ⎝ g ⎠ and g(x) ≠ 0
  • 7. x−4 x−3 Example: f (x) = g(x) = x −1 x−2
  • 8. x−4 x−3 Example: f (x) = g(x) = x −1 x−2 x−4 x−3 ( f + g)(x) = + D: {x : x ≠ 1,2} x −1 x − 2
  • 9. x−4 x−3 Example: f (x) = g(x) = x −1 x−2 x−4 x−3 ( f + g)(x) = + D: {x : x ≠ 1,2} x −1 x − 2 x−4 x−3 ( f − g)(x) = − D: {x : x ≠ 1,2} x −1 x − 2
  • 10. x−4 x−3 Example: f (x) = g(x) = x −1 x−2 x−4 x−3 ( f + g)(x) = + D: {x : x ≠ 1,2} x −1 x − 2 x−4 x−3 ( f − g)(x) = − D: {x : x ≠ 1,2} x −1 x − 2 ⎛ x − 4 ⎞ ⎛ x − 3 ⎞ ( f ⋅ g)(x) = ⎜ ⎝ x − 1 ⎟ ⎜ x − 2 ⎟ ⎠ ⎝ ⎠ D: {x : x ≠ 1,2}
  • 11. x−4 x−3 Example: f (x) = g(x) = x −1 x−2 x−4 x−3 ( f + g)(x) = + D: {x : x ≠ 1,2} x −1 x − 2 x−4 x−3 ( f − g)(x) = − D: {x : x ≠ 1,2} x −1 x − 2 ⎛ x − 4 ⎞ ⎛ x − 3 ⎞ ( f ⋅ g)(x) = ⎜ ⎝ x − 1 ⎟ ⎜ x − 2 ⎟ ⎠ ⎝ ⎠ D: {x : x ≠ 1,2} ⎛ f ⎞ ⎛ x − 4 ⎞ ⎛ x − 2 ⎞ ⎜ g ⎟ (x) = ⎜ x − 1 ⎟ ⎜ x − 3 ⎟ ⎝ ⎠ ⎝ ⎠ D: {x : x ≠ 1,2, 3} ⎝ ⎠
  • 12. x−4 x−3 Example: f (x) = g(x) = x −1 x−2 x−4 x−3 ( f + g)(x) = + D: {x : x ≠ 1,2} x −1 x − 2 x−4 x−3 ( f − g)(x) = − D: {x : x ≠ 1,2} x −1 x − 2 ⎛ x − 4 ⎞ ⎛ x − 3 ⎞ ( f ⋅ g)(x) = ⎜ ⎝ x − 1 ⎟ ⎜ x − 2 ⎟ ⎠ ⎝ ⎠ D: {x : x ≠ 1,2} ⎛ f ⎞ ⎛ x − 4 ⎞ ⎛ x − 2 ⎞ ⎜ g ⎟ (x) = ⎜ x − 1 ⎟ ⎜ x − 3 ⎟ ⎝ ⎠ ⎝ ⎠ D: {x : x ≠ 1,2, 3} ⎝ ⎠ Be sure to read Example 2 in your textbook
  • 14. Composite Functions The output of one function (the inner function) is used as input for another function (the outer function) notation : f ( g ( x ))
  • 15. Composite Functions The output of one function (the inner function) is used as input for another function (the outer function) notation : f ( g ( x )) Example 1: y = x +1
  • 16. Composite Functions The output of one function (the inner function) is used as input for another function (the outer function) notation : f ( g ( x )) Example 1: y = x +1 Inner function is done first x +1 Outer function is done second x
  • 17. Composite Functions The output of one function (the inner function) is used as input for another function (the outer function) notation : f ( g ( x )) Example 1: y = x +1 Inner function is done first x +1 Outer function is done second x g(x) = x + 1 f (x) = x f (g(x)) = x + 1
  • 19. Composite Functions Example 2: y = sin ( 3θ ) Inner 3θ g(θ ) = 3θ
  • 20. Composite Functions Example 2: y = sin ( 3θ ) Inner 3θ g(θ ) = 3θ Outer sin ( x ) f (x) = sin ( x )
  • 21. Composite Functions Example 2: y = sin ( 3θ ) Inner 3θ g(θ ) = 3θ Outer sin ( x ) f (x) = sin ( x ) f (g(θ )) = sin ( 3θ )
  • 23. Composite Functions Example 3: y = sin 2 (θ ) Inner sin (θ ) g(θ ) = sin (θ )
  • 24. Composite Functions Example 3: y = sin 2 (θ ) Inner sin (θ ) g(θ ) = sin (θ ) Outer x 2 f (x) = x 2
  • 25. Composite Functions Example 3: y = sin 2 (θ ) Inner sin (θ ) g(θ ) = sin (θ ) Outer x 2 f (x) = x 2 f (g(θ )) = sin 2 (θ )
  • 26. Composite Functions Example 4: y = sin 2 ( 3θ )
  • 27. Composite Functions Example 4: y = sin 2 ( 3θ ) Innermost 3θ h(θ ) = 3θ
  • 28. Composite Functions Example 4: y = sin 2 ( 3θ ) Innermost 3θ h(θ ) = 3θ Next Inner sin (θ ) g(θ ) = sin (θ )
  • 29. Composite Functions Example 4: y = sin 2 ( 3θ ) Innermost 3θ h(θ ) = 3θ Next Inner sin (θ ) g(θ ) = sin (θ ) Outer x 2 f (x) = x 2
  • 30. Composite Functions Example 4: y = sin 2 ( 3θ ) Innermost 3θ h(θ ) = 3θ Next Inner sin (θ ) g(θ ) = sin (θ ) Outer x 2 f (x) = x 2 f (g(h(θ ))) = sin 2 ( 3θ )
  • 31. Composite Functions Example 4: y = sin 2 ( 3θ ) Innermost 3θ h(θ ) = 3θ Next Inner sin (θ ) g(θ ) = sin (θ ) Outer x 2 f (x) = x 2 f (g(h(θ ))) = sin 2 ( 3θ ) Be sure to read Example 7 in your textbook
  • 32. Is f (g(x)) = g( f (x)) ?
  • 33. Is f (g(x)) = g( f (x)) ? Let f(x) = 2x+1 g(x) = x-3
  • 34. Is f (g(x)) = g( f (x)) ? Let f(x) = 2x+1 g(x) = x-3 f (g(x)) = 2(x − 3) + 1 = 2x − 6 + 1 = 2x − 5
  • 35. Is f (g(x)) = g( f (x)) ? Let f(x) = 2x+1 g(x) = x-3 f (g(x)) = 2(x − 3) + 1 g( f (x)) = (2x + 1) − 3 = 2x − 6 + 1 = 2x − 2 = 2x − 5
  • 36. Is f (g(x)) = g( f (x)) ? Let f(x) = 2x+1 g(x) = x-3 f (g(x)) = 2(x − 3) + 1 g( f (x)) = (2x + 1) − 3 = 2x − 6 + 1 = 2x − 2 = 2x − 5 Not the same
  • 37. Is f (g(x)) = g( f (x)) ? Let f(x) = 2x+1 g(x) = x-3 f (g(x)) = 2(x − 3) + 1 g( f (x)) = (2x + 1) − 3 = 2x − 6 + 1 = 2x − 2 = 2x − 5 Not the same Could they be the same?
  • 38. Could f (g(x)) = g( f (x)) ?
  • 39. Could f (g(x)) = g( f (x)) ? x −1 Let f (x) = 2x + 1 and g(x) = 2
  • 40. Could f (g(x)) = g( f (x)) ? x −1 Let f (x) = 2x + 1 and g(x) = 2 ⎛ x − 1 ⎞ f (g(x)) = 2 ⎜ ⎟ + 1 ⎝ 2 ⎠ = x − 1+ 1 =x
  • 41. Could f (g(x)) = g( f (x)) ? x −1 Let f (x) = 2x + 1 and g(x) = 2 ⎛ x − 1 ⎞ (2x + 1) − 1 f (g(x)) = 2 ⎜ ⎟ + 1 g( f (x)) = ⎝ 2 ⎠ 2 2x = x − 1+ 1 = 2 =x =x
  • 42. Could f (g(x)) = g( f (x)) ? x −1 Let f (x) = 2x + 1 and g(x) = 2 ⎛ x − 1 ⎞ (2x + 1) − 1 f (g(x)) = 2 ⎜ ⎟ + 1 g( f (x)) = ⎝ 2 ⎠ 2 2x = x − 1+ 1 = 2 =x =x These are the same. It happens when f(x) and g(x) are inverses of each other.
  • 43. HW #9 “There are precious few Einsteins among us. Most brilliance arises from ordinary people working together in extraordinary ways.” Roger Von Oech

Editor's Notes